Introduction to MIPS Assembly Language Programming - Kann, Charles (Open textbook library., 2016)
This book was written to introduce students to assembly language programming in MIPS. As with all assemblylanguage programming texts, it covers basic operators and instructions, subprogram calling, loading andstoring memory, program control, and the conversion of the assembly language program into machine code. However this book was not written simply as a book on assembly language programming. The larger purposeof this text is to show how concepts in Higher Level Languages (HLL), such as Java or C/C++, arerepresented in assembly. By showing how program constructs from these HLL map into assembly, theconcepts will be easier to understand and use when the programmer implements programs in languages likeJava or C/C++. Concepts such as references and variables, registers, binary and Boolean operations, subprogram execution, memory types (heap, stack, and static), and array processing are covered to clarify thedecisions made when implementing HLL. Program control is presented using a mapping from structuredprograms in pseudo code to help students understand structured programming, and why it exists. Memoryaccess in assembly is presented to high light the difference between references (pointers) and values, and howthese impact HLL. This book has numerous code examples, and many problems at the end of each chapter, and it is appropriate for a class in Assembly Language, or as a extra resource for a class in Computer Organization.